Educational indications for children in the light of Eph 6, 1–3 - Kułaczkowski, Jerzy (Paedagogia Christiana, 2009)
Researching some sources, which might be helpful witch precisely to the definition of educational indications is always actual topic, because of a permanent need of bringing up the human being. It is particularly important nowadays when it could be easily seen crisis of education and its effects, especially inappropriate treated parents by children. For such a source might be treated the Holy Bible, that is a revealed Word of God, included also many of educational indications. One of them is text is Eph 6, 1–3. In the light of this text children are particularly obliged to obedience to their parents. Motive of this behaviour is a commandment of God. The basic of this commandment is justice. Children are also obliged to respect their parents, because bringing up the children is a mission given to parents by God. Through it they participate in God`s activity of salvation. Respecting parents by children is moreover strengthened by the promise of earthly happiness. Presented at Eph 6,1–3 educational indications for children concerning their behaviour to their parents, might be a precious help also at present times in a front of loosing a proper regarding of parents by children.